2013
DOI: 10.1186/1472-6785-13-20
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory of an invasive slug is affected by earthworms and the composition of plant communities

Abstract: BackgroundBiodiversity loss and species invasions are among the most important human-induced global changes. Moreover, these two processes are interlinked as ecosystem invasibility is considered to increase with decreasing biodiversity. In temperate grasslands, earthworms serve as important ecosystem engineers making up the majority of soil faunal biomass. Herbivore behaviour has been shown to be affected by earthworms, however it is unclear whether these effects differ with the composition of plant communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
2
17
1
1
Order By: Relevance
“…Moreover, the species is used to test predictions on invasive species success, for example, regarding phenotypic plasticity (Knop and Reusser ) and diet choice (Zaller et al. ) or as an example of their impact (e.g. Blattmann et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the species is used to test predictions on invasive species success, for example, regarding phenotypic plasticity (Knop and Reusser ) and diet choice (Zaller et al. ) or as an example of their impact (e.g. Blattmann et al.…”
Section: Discussionmentioning
confidence: 99%
“…Moss and Hermanutz 2010) or even eradication efforts crucially depend on whether a species is introduced or native (see respective paragraphs in, e.g., the Convention on Biological Diversity or the Convention on Migratory Species of Wild Animals). Moreover, the species is used to test predictions on invasive species success, for example, regarding phenotypic plasticity (Knop and Reusser 2012) and diet choice (Zaller et al 2013) or as an example of their impact (e.g. Blattmann et al 2013), which is questionable given the presented results.…”
Section: Discussionmentioning
confidence: 99%
“…Zaller et al . () found that slug herbivory is affected by an interaction between earthworms and plant diversity. Plant communities varied across our study sites and were affected by earthworm abundance (A. Dávalos, V. Nuzzo & B. Blossey, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…Once again (see results for non-native plant and slug interaction on Agrimonia survival), we found that slug presence had a positive effect on survival in more stressful conditions only, in this case at low earthworm abundance sites (earthworms have a positive effect on Agrimonia). Zaller et al (2013) found that slug herbivory is affected by an interaction between earthworms and plant diversity. Plant communities varied across our study sites and were affected by earthworm abundance (A.…”
Section: Discussionmentioning
confidence: 99%
“…This species exhibits superior mobility (Honek & Martinkova, ; Knop et al, ) and is well adapted to warm and dry microclimates (Knop & Reusser, ); consequently, it survives well on farmland (Ryser et al, ). The presence of populations of this slug on degraded areas (construction sites, roadside margins) that are typical A. sagittata habitats is supplied by emigrants from near grassy sites (Honek & Martinkova, ) and might be favoured due to an impoverishment of the soil fauna (Zaller et al, ). The consequences of recent A. vulgaris invasion increase the risk of death for A. sagittata .…”
Section: Discussionmentioning
confidence: 99%